Volume 7: Turbomachinery, Parts A, B, and C 2011
DOI: 10.1115/gt2011-45637
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Analysis of the Effect of Variable Blade Row Spacing in a Subsonic Axial Turbine

Abstract: Numerical and experimental investigations have been performed to determine the effect of a variation of the inter blade row axial gap on turbine efficiency. The geometry used in this study is the 1.5 stage axial flow turbine rig of the Institute of Jet Propulsion and Turbomachinery at RWTH Aachen University. The influence of the blade row spacing on aerodynamics has been analyzed by conducting steady and unsteady RANS simulations as well as measurements in the cold air turbine test rig of the Institute. Both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…According to the open literature, this trend is confirmed by some authors [42][43][44][45][46] but seems not general (as also reported and discussed by [41]), either for a lack of detailed data or for a case dependency in the stator wake-potential field coupling along the axial direction, in the axial gap region.…”
Section: Axial Gapmentioning
confidence: 73%
“…According to the open literature, this trend is confirmed by some authors [42][43][44][45][46] but seems not general (as also reported and discussed by [41]), either for a lack of detailed data or for a case dependency in the stator wake-potential field coupling along the axial direction, in the axial gap region.…”
Section: Axial Gapmentioning
confidence: 73%
“…Five of the test cases are single-stage turbines and two are 1.5 stage machines. Restemeier et al 9 suggest that the second stator and the preceding axial clearance only has a minimal influence on the loss differences between the cases with different axial clearances. With this assumption, a direct comparison of single and 1.5 stage turbines is reasonable and a possible small error does not have a notable influence on the accuracy of the current analysis.…”
Section: Analysed Data and Linear Correlation Methodsmentioning
confidence: 99%
“…After this assumption, the correlations between the two parameters from Table 1 and the slopes of efficiency were evaluated. 9 1.31 0.45 Meas. Venable et al 10 4.84 1.10 URANS Chang and Tavoularis 19 -1.18 URANS Yamada et al 24 3.99 0.18 Meas.…”
Section: Analysed Data and Linear Correlation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From experimental investigations conducted by Bohn et al 13 , it is furtherly known, that the use of a special miniature pneumatic probe for the correction of former probe measurements was necessary since former measurements with a larger probe had been found incorrect due to severe probe-flow interaction fudging the results for the flow field measurements in a 4-stage axial turbine. Restemeier et al 11 conducted numerical calculations as well as experimental investigations on a 1.5-stage axial turbine with very low aspect ratio and for different axial-gap configurations, in order to investigate the influence of different axial spacings between blade rows. His changes to the axial positions of the vane rows led to numerically predicted differences of Δη=0,6%.…”
Section: Introductionmentioning
confidence: 99%